Design of a Computerized Fence at Nyabikoni Campus Kabale University. - Twinamasiko, Joshua (Kabale University, 2023)
This report is about a design of a perimeter fence for Kabale University Nyabikoni Campus. The writing here in this report contains three chapters; Chapter 1 is the introduction of the proposal that states the contents of the background of the project, how the problem was identified and why the project viable. Chapter 2 contains the literature review, works and related information by other scholars about design mainly architectural working drawings. Chapter 3 outlines the methodology of how the project was done; these are sequential methods for the process. Chapter 4 discusses the challenges, recommendations, appendices, reference and other photos related with the project.